Toe walking in children with autism spectrum disorder and comorbid attention deficit hyperactivity disorder: An early marker of a heterogeneous disorder? - Adeniyi, Yetunde Celia; Adeniyi, Ade Fatai; Oyewole, Olugboyega Abimbola (Indian Journal of Case Reports, 2020)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder (NDD). Toe walking has been reported in children with NDDs. However, the relationship between ASD and toe walking is still unclear. The aim of the paper is to describe toe walking in four children with ASD and comorbid attention deficit hyperactivity disorder (ADHD). Their age ranged between 28 months and 42 months and three of the cases had moderate to severe toe walking on both feet. All the cases scored in the high-risk category (8–20) of the Modified Checklist for Autism in Toddlers and above the cut-off scores (24 for girls and 32 for boys) of the ADHD RS-IV-P. In addition, they all met DSM-V diagnostic criteria for ASD and ADHD. Clinicians diagnosing ASD may be omitting an important element of the disorder in the form of toe walking, which could contribute to delayed or inaccurate diagnoses. Consideration of including motor function deficits such as toe walking in the diagnostic criteria for ASD might improve early detection and intervention.